Navigating interprofessional collaboration in diabetes care: A qualitative study of early-career health professionals in malaysian primary care clinics - Kelly Sze Fang Num; Azimatun Noor Aizuddin; Syahnaz Mohd Hashim; Mohd Shahrir Mohamed Said (PLoS ONE, 2025)
Introduction Interprofessional collaborative care (IPC) is essential for effective healthcare delivery, particularly in managing chronic conditions such as diabetes in primary care settings. However, early-career health professionals (ECHPs) often encounter significant challenges when establishing effective IPC, given its inherent complexity. This study explores how ECHPs in primary care clinics navigate and engage in IPC for diabetes management. Methods A qualitative study was conducted from 1 st December 2021–1 st October 2022 at two Malaysian primary care clinics (urban and suburban). Seven ECHPs meeting predefined criteria (6 months to 5 years’ experience, no postgraduate degree) were purposively sampled and interviewed until data saturation. In-depth semi-structured interviews (face-to-face or virtually via Zoom), conducted in either English or Malay, were audio- or video-recorded and transcribed verbatim. Data were analyzed using Braun and Clarke’s reflexive thematic analysis with constant comparison to ensure rigor. Results Seven main themes emerged regarding how ECHPs in primary care clinics navigate and engage in interprofessional collaborative practices: (1) Initiating and continuing dialogue, (2) Creating cohesiveness, (3) Effective ways of communication, (4) Having own personal values, (5) Willing to work synergistically, (6) Learning from each other, and (7) Embracing diversities and resolving conflict. These themes represent interrelated components that ECHPs had adopted to effectively engage in interprofessional collaborative practices. Conclusion IPC in diabetes management is a complex system requiring ECHPs to employ interrelated components for effective engagement. ECHPs overcame hierarchical barriers through proactive dialogue, reflecting a shift toward egalitarian teamwork. Digital platforms aided coordination, though face-to-face interactions were preferred for complex cases and direct communication. Team cohesion was strengthened through shared leadership, conflict resolution, and interprofessional learning, enabling ECHPs to adapt and contribute confidently. Educational institutions should integrate emotional intelligence, negotiation skills and digital ethics into IPC curricula. Healthcare organizations must reinforce collaborative practices through policies, mentorship and structured training to bridge theory-practice gaps. Future research should explore informal socialization, peer coaching and long-term digital communication impacts to strengthen IPC support for ECHPs.